Comparison of energy cost between genders during treadmill walking at a self-selected pace - doi 10.4025/actascihealthsci.v34i2.9333 (Acta Scientiarum. Health Sciences, 2012)
The purpose of this study was to compare the energy cost between genders during treadmill walking at self-selected pace; and to verify if the energy cost achieve the values recommended for weight maintenance or loss proposed by the American College of Sports Medicine (ACSM). Seventeen men and seventeen women, mean age of 23.32 ± 3.06 years, undertaken two experimental sessions: (I) anthropometric measurements and a load-incremental maximum test; and, (II) a 20-min walking test at self-selected pace on treadmill. Men showed a greater energy cost than women (146.18 ± 47.66 and 100.86 ± 17.04 kcal, respectively). This difference was maintained after adjust by body weight (2.2 ± 0.5 and 1.7 ± 0.2 kcal kg-1, respectively). The greater energy cost found in men can be explained by the self-selected treadmill speed that lead to a greater O2 in men. However, the exercise intensity selected by both genders did not elicit an effective energy cost that can promote weight maintenance or loss. Nonetheless, if participants performed a longer walking (> 20 minutes), they probably would achieve the energy cost recommended by the ACSM guidelines.